The Impact of Digitization on the Spanish Publishing Industry - Magadán Díaz, Marta; Rivas García, Jesús Israel (International Journal of the Book, 2019)
The purpose of this article is to analyze the impact of technological change on the Spanish publishing industry and to see how the industry is adapting to the new digital environment. This work provides deep insight into the Spanish publishing industry through the collection and grouping of the available data, mainly from public and private secondary sources of information, in order to generate a time series that allows a glimpse of the state and evolution of digitization in the Spanish publishing industry over the last twenty years. This work also examines the new business models emerging from digitization, before closing with some conclusions, recommendations for the publishing industry, and suggestions for future lines of research. This study is not intended to be a history of the past, present, and future of the book industry in Spain, but rather, is the first step in a deeper analysis of the Spanish publishing industry.
Keywords: Scopus